Coexistence of Lateriporus teres (Cestoda: Dilepididae) and Polymorphus phippsi (Palaeacanthocephala: Polymorphidae) in the intestine of common eider - М. М. Kuklina; V. V. Kuklin (Российский паразитологический журнал, 2021)
The purpose of the research is studying the peculiarities of parasite infection of the cestodes Lateriporus teres Krabbe, 1869 (Cestoda: Dilepididae) and acanthocephalans Polymorphus phippsi Kostylew, 1922 (Palaeacanthocephala: Polymorphidae) during coexistence in the intestine of the common eider, particularly, the localization of these parasites, the activity of protein and carbohydrate metabolism enzymes on the tegument of the worms, the degree of parasite influence on the host digestion, as well as to assess total digestive activity in the gastrointestinal tract of birds infected with these helminths.Materials and methods. Using methods of biochemical analysis, the activity of digestive enzymes (protease and glycosidase) and the intensity of a digestion with the participation of these enzymes along the intestine of the common eider were determined. The digestive activity of enzymes in the body of helminthes was measured, and the intensity of membrane digestion on the surface of their tegument was estimated.Results and discussion. During coexistence, L. teres were observed mainly in the proximal parts of the intestine of the birds, P. phippsi in the distal parts. Membrane digestion, involving the action of proteases and glycosidases, occurred on the surface of the tegument of both cestodes and acanthocephalans. The protein metabolism intensity in both helminth species was nearly the same, but the glycosidase activity was higher on the tegument of L. teres. The glycosidase activity in the body of the acanthocephalans exceeded that in the cestodes strobile six times. In the intestine parts inhabited by L. teres, both protease and glycosidase activity decreased. In the intestine parts where P. phippsi parasitized, protease activity increased in the intestinal mucosa of the common eider. The total activity of protease and glycosidase along the entire length of the intestine in common eider infected with L. teres and P. phippsi was lower compared to the uninfected birds.